(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
This theoretical research aims to analyze the changes in the administrative management control of the Legislative Councils in Venezuela, from the perspective of institutional sustainability. In order to do so, we used several theories that allowed us to develop the ontological aspect, such as the Institutional Theory (North 1990), Theory of Management Control (Fayol, 1961; Anthony, 1990; Koontz and Weihrich, 1985); Theory of Sustainable Development (Godard, 2002; Schumacher, 1973) and The Theory of Institutional Sustainability (De Souza, 2001). The conclusion shows that institutional sustainability in terms of Legislative Councils translates into a social recognition and political, institutional and financial support obtained as a result of a process of permanent interaction and negotiation with key actors in their environment.